AB0580 GENDER DIFFERENCES IN SYSTEMIC SCLEROSIS- IMPACT ON DISEASE PHENOTYPE AND PROGNOSIS. (2nd June 2020) - Groseanu, L.; Balanescu, A.; Bojinca, V.; Opris-Belinski, D.; Saulescu, I.; Mazilu, D.; Daia-Iliescu, S.; Borangiu, A.; Berghea, F.; Constantinescu, C. L.; Cobilinschi, C.; Negru, M. M.; et al.
Abstract : Background: The low overall prevalence of systemic sclerosis (SSc) and the low proportion of male patients have resulted in a scarcity of studies assessing sex differences in SSc patients, and contradictory results. Objectives: To evaluated sex influence on disease characteristics at baseline and then to estimate the effects of sex on disease progression and survival. Methods: We performed a retrospective observational study using data extract from the EULAR scleroderma trials and research (EUSTAR) cohort 096. 173 patients were analysed (26 males). The severity of organ system involvement was defined as described previously (1). Results: Males were significantly older at symptom onset (p=0.007) and at first center visit (p=0.009). There were no differences regarding disease duration at first visit or the interval between the onset of Raynaud syndrome and other non-Raynaud manifestations (p=0.06). Male patients were significantly more likely to have ever smoked (p<0.001), males more often had severe or end-stage peripheral vascular involvement (p=0.01). Modified Rodnan skin score (mRSS) was significantly higher in males (p=0.004). We found no difference regarding musculoarticular involvement, except for digital contractures (p=0.001) and tendon friction rubs (p=0, 044). Males more often had interstitial lung disease (ILD) (p=0.013) which was also more frequently severe or end-stage (p = 0.003). Cardiac involvement was more common in males: pulmonary hypertension (PAH) (p = 0.018), arrhytmias (p=0.012), left ventricle ejection fraction<45% (p=0.014). The frequency of scleroderma renal crisis (SRC) was higher in males (p=0.025). Gastrointestinal involvement did not differ between groups EScSG (European Scleroderma Study Group) disease activity scores were higher in males (p=0.001). The isolated presence of antitopoisomerase-1 or anticentromere antibodies did not differ between groups. Mortality rate was similar between sexes, although male sex is a independent predictor for the death associated with ILD, SRC, arrythmias In multivariate analysis, male sex was independently associated with a higher risk of diffuse cutaneous subtype (OR: 1.56, (1.35 to 1.84); p<0.001), a higher frequency of severe vascular disease (OR: 1.38 (1.11 to 1.67); p<0.001), severe digital contractures (OR:1.92(1.68 to 2, 42); p<0.001), interstitial lung disease OR: 1.22 (0.9 to 1.47); p<0.001), severe heart involvement (OR: 1.56 (1.22 to 2, 1); p<0.001) and SRC (OR: 3.31 (1.87 to 5620); p<0.003). In the longitudinal analysis, after a mean follow-up of 7.2 (±2.6) years, male sex was predictive of new onset of scleroderma renal crisis (HR: 3.66 (1.82 to 4.86); p=0.006) and heart failure (HR: 1.9 (1.36 to 3.18); p=0.01). Conclusion: In essence, the disease prophyle in females is that of younger age of onset, longer disease duration at first center visit, less severe peripheral vascular involvement, the most frequent cause of death being PAH. In contrast, males are older at onset, present earlier in their disease, have dcSSc, more severe peripheral vascular disease, higher mRSS, more frequent and severe ILD, more frequent heart involvement, higher risk of PAH and SRC, the most common cause of death being ILD. These results raise the point of including sex in the management and the decision-making process. References: [1]Peoples C, Medsger TA Jr, Lucas M et al Gender differences in systemic sclerosis: relationship to clinical features, serologic status and outcomes. J Scleroderma Relat Disord . 2016;1(2):177–240 Disclosure of Interests: Laura Groseanu Speakers bureau: novartis, eli-lilly, ucb, pfizer, sandoz, Andra Balanescu Consultant of: pfizer, Speakers bureau: Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, UCB, Violeta Bojinca Speakers bureau: Eli-Lilly, Novartis, Pfizer, Daniela Opris-Belinski Speakers bureau: Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Ioana Saulescu Speakers bureau: Eli-Lilly, Pfizer, Diana Mazilu: None declared, Sanziana Daia-Iliescu Speakers bureau: sandoz, Andreea Borangiu: None declared, Florian Berghea Paid instructor for: abbvie, Speakers bureau: gideon richter, egis, novartis, ucb, cosmin-laurentiu constantinescu: None declared, CLAUDIA COBILINSCHI Speakers bureau: novartis, Maria Magdalena Negru: None declared, mihai abobului Speakers bureau: gideon richter, Ruxandra Ionescu Consultant of: Consulting fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, Speakers bureau: Consulting and speaker fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz